A HYDROLOGIC MODEL FOR A CRATER LAKE ON MALYI SEMYACHIK VOLCANO (KAMCHATKA) - Gavrilenko G.M. (My University, 2001)
A hydrologic model is offered for a drainless lake in the crater of an active volcano based on the observation data derived in the crater lake of the Malyi Semyachik volcano. This model was used to calculate a number of parameters characterizing the state of the crater lake during different phases of the volcano's activity. It is shown that the water balance in drainless crater lakes is controlled during all phases of volcanic activity by an underground water discharge which is a function of the lake floor area and, hence, of the lake volume. It was found that the seasonal variations of the water level in the crater lake of the Malyi Semyachik volcano during its active phases were not greater than ±2 m, which is insignificant compared with the significant rise of water in the lake caused by the addition of water supplied by the endogenic fluid.